A new species of tick (Acari: Ixodidae) from seabirds in New Zealand and Australia, previously misidentified as Ixodes eudyptidis - Heath, Allen C.g.; Palma, Ricardo L. (Zootaxa, 2017)
The tick Ixodes eudyptidis Maskell, 1885 has long been recognised as a parasite of penguins and a number of other seabird hosts and, despite a convoluted taxonomic history, there has been no disagreement as to its validity. The opportunity to examine a larger series of ticks from a wider range of hosts than previously available has led to the finding of a morphologically close and hitherto undescribed species, which is herewith described and named as Ixodes laridis sp.nov. The new species has a superficial similarity to its sibling, I. eudyptidis, but on close examination it displays a number of morphological differences that justify its taxonomic separation. Also, the hosts of the new species are principally gulls, gannets and cormorants, while I. eudyptidis is restricted to penguins. The recognition of this new species has implications for faunal lists in both New Zealand and Australia, as well for seabird health, as it appears that I. eudyptidis does not cause paresis as originally thought, but it is I. laridis that causes potentially fatal paralysis in its hosts. A taxonomic history and review of I. eudyptidis and keys to all stages of the species of Ixodes recorded from New Zealand, and from Australian seabirds are given. Reference to Ixodes kohlsi Arthur, 1955, a species currently restricted to Australia, is made for comparative purposes because of the similarity of both its morphology and host associations with the other species under consideration. Aspects of the distribution, zoogeography, hosts and ecology of all three species of ticks are discussed.